Voltage Profile Improvement of Distribution System via Integration of Distributed Generation Resources - Pokhrel, Biswas Babu; Shrestha, Ashish; Phuyal, Sudip; Jha, Shailendra Kumar (Institute for Research and Community Service, Universitas Malikussaleh, Indonesia, 2021)
This study attempts to identify the causes and possible solutions for voltage profile issues in the lower land of Nepal, and is specifically focused on Laukahi feeder, a radial distribution system with an approximate length of 65 km and distributed at 11KV system voltage. Currently, the end-users feeding through this feeder are getting extremely poor voltage along with frequent interruptions in the power supply. In this study, a forward/ backward sweep algorithm is used to analyze the load flow of the distribution system, whereas ant colony optimization (ACO) technique is used to identify the best location for the Distributed Generator (DG) penetrations. After completion of this study, it is found that, the branch loss of the feeder can be reduced up to 87.22%, and voltage profile can be improved from 0.828 pu to 0.982 pu by integrating some form of DGs.